Scientific Integration and its Application to The Curriculum - Busahdiar, Busahdiar; Syah, Muhibbin; Arief, Armai; Erihadiana, Mohamad (Green Publisher Indonesia, 2024)
This research is motivated by the transformation of IAIN Syarif Hidayatullah Jakarta into UIN Syarif Hidayatullah Jakarta which cannot be separated from the mission to integrate general science and religious science. However, in its implementation, this scientific integration needs to be researched whether it is in accordance with the ideal formula into the empirical-operational area, especially in the preparation and development of the curriculum, especially in the Faculty of Dirasat Islamiyah and the Faculty of Medicine UIN Syarif Hidayatullah Jakarta. Therefore, this research is focused on the integration of science and its application to the curriculum, especially in the two faculties. Therefore, this study aims to identify the objectives, planning, implementation, evaluation and supervision process, supporting and inhibiting factors and the impact of scientific integration on the quality of graduates in the two faculties. The approach used is a qualitative approach. The research method used is descriptive analysis. The data obtained through this study is empirical (observed) data that has certain criteria that are valid, reliable and objective. Data collection was carried out by interviews, observations and document studies. The data analysis technique is through; data reduction, data display and drawing conclusions. The results of the study showed; (1) the purpose of the Faculty of Dirasat Islamiyah is to integrate its science in order to realize the vision and mission of UIN Jakarta, while the purpose of the Faculty of Medicine in integrating its science is to realize the goal of the establishment (winder manded) of UIN Jakarta itself.